(untitled) (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The aim of this study was to estimate genetic parameters, breeding value, and ranking of Holstein Friesian × Local (HF × L) crossbred sires based on multi-trait selection index information. Methods: A total of 51 HF × L crossbred breeding bulls of three different genetic groups (50%HF × 50%L, 62.5%HF × 37.5%L, and 75%HF × 25%L) managed at Central Cattle Breeding and Dairy Farm (CCBDF) were evaluated based on 4,319 half-sib progeny performance data. The descriptive statistical analysis was performed using the R package. Genetic parameters were estimated using BLUPF90 by a single-trait animal model. A selection index was constructed using adjusted breeding values multiplied by variable economic weightage for each trait. Results: Genotype had significant effects on the investigated semen quality attributes (p < 0.05), where 75%HF × 25%L and 62.5%HF × 37.5%L crossbred genotypes both differed significantly from 50%HF × 50%L crossbreds (p < 0.05). In general, better productive and reproductive performances were found with the progression of HF inheritance. Daughters of 75%HF × 25%L crossbred bulls showed the highest average performance in birth weight (27.20 ± 0.09 kg), daily milk yield (8.55 ± 0.06 l), peak milk yield (10.44 ± 0.07 l), and lactation length (233.53 ± 0.85 days). The study investigated variance components of eight productive and reproductive traits such as the birth weight of calf, age at first conception, service per conception, daily milk yield, peak milk yield, lactation length, and calving interval where estimated heritability ranged from 0.09 to 0.32. Genetic correlations among the considered traits were found to be mostly weak. Among the top 20%, breeding bulls belonged to 75%HF × 25%L and 62.5%HF × 37.5%L crossbred groups. Conclusion: This study provides insightful information on the genetic evaluation of different graded bulls that could be the basis for the proven crossbred breeding bulls’ selection process at CCBDF. J. Adv. Vet. Anim. Res., 12(2): 334–343, June 2025 http://doi.org/10.5455/javar.2025.l901